Associations of co-exposure to polycyclic aromatic hydrocarbons and metals with hyperuricemia risk in Chinese coke oven workers: Mediating roles of oxidative damage - Guo, Chaofan; Liu, Xin; Liao, Xiaojing; Wu, Haimei; Zhang, Zhaorui; Wu, Dehua; Ma, Rui; Huang, Yongshun; Zhao, Na; Xiao, Yongmei; Deng, Qifei (Environmental pollution (1987), 2023)
Ubiquitous polycyclic aromatic hydrocarbons (PAHs) and metals could induce hyperuricemia and oxidative damage individually, while their co-exposure effects on hyperuricemia risk and the potential roles of oxidative damage in these health outcomes remain poorly understood. We conducted a cross-sectional study in 1379 coke oven workers. We evaluated the levels of PAH-metal exposure and oxidative damage by urinary monohydroxy-PAHs, plasma benzo [a]pyrene-7,8-diol-9,10-epoxide-albumin (BPDE-Alb) adducts, urinary metals, urinary 8-iso-prostaglandin-F2α, and urinary 8-hydroxydeoxyguanosine (8-OH-dG). The subjects were classified into cases of hyperuricemia and controls by the levels of blood uric acid. We found that the sum of multiple hydroxyphenanthrene (ΣOH-Phe) was robustly associated with the increase in hyperuricemia risk, while rubidium and strontium had robust protective associations with hyperuricemia risk (Ptrend<0.05). The risk association of ΣOH-Phe was weaker in workers with high levels of rubidium and strontium [P for modifying effect (PME) < 0.030]. The protective association of strontium was more pronounced in workers with higher ΣOH-Phe (PME = 0.014). We also found that 8-OH-dG was a risk factor for hyperuricemia (Ptrend = 0.006) and mediated 10.13% of the elevated hyperuricemia risk associated with ΣOH-Phe. Our findings suggested that individual PAHs and metals, as well as their co-exposure, may influence hyperuricemia risk among coke oven workers, with oxidative DNA damage playing a potential mediating role in their associations. [Display omitted] •ΣOH-Phe was robustly associated with the increase of hyperuricemia risk.•Rubidium and strontium had robust protective associations with hyperuricemia risk.•Risk association of ΣOH-Phe was weaker in workers with high rubidium and strontium.•Protective association of strontium was stronger in workers with high ΣOH-Phe.•8-OH-dG mediated 10.13% of elevated hyperuricemia risk associated with ΣOH-Phe.